2013
DOI: 10.1017/pasa.2013.25
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Frequency Allocation for Radio Astronomy at the L Band

Abstract: In this paper, the frequency allocation reserved for radio astronomy in the L band set by the International Telecommuni-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The study was done in Malaysia and Thailand, and it was found that the interferences come from electronic equipment especially radio navigation (731 MHz until 752 MHz), radio broadcasting (151 MHz, 151.8 MHz and 152 MHz), aeronautical navigation (245.5 MHz, 248.7 MHz and 249 MHz) and fixed mobile (605 MHz, 608.3 MHz, 612.2 MHz and 613.3 MHz). At the same time, it was observed that the frequency band of 320 MHz until 330 MHz were free from interferences and best band to conduct the solar burst observation [7], [8], [20]. Several radio astronomical lines with their own rest frequency in the radio band as listed by MCMC and ITU were shown in this paper.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The study was done in Malaysia and Thailand, and it was found that the interferences come from electronic equipment especially radio navigation (731 MHz until 752 MHz), radio broadcasting (151 MHz, 151.8 MHz and 152 MHz), aeronautical navigation (245.5 MHz, 248.7 MHz and 249 MHz) and fixed mobile (605 MHz, 608.3 MHz, 612.2 MHz and 613.3 MHz). At the same time, it was observed that the frequency band of 320 MHz until 330 MHz were free from interferences and best band to conduct the solar burst observation [7], [8], [20]. Several radio astronomical lines with their own rest frequency in the radio band as listed by MCMC and ITU were shown in this paper.…”
Section: Introductionmentioning
confidence: 90%
“…According to [7], [8], they found that the major effect of RFI on astronomical lines is below 1 GHz. The study was done in Malaysia and Thailand, and it was found that the interferences come from electronic equipment especially radio navigation (731 MHz until 752 MHz), radio broadcasting (151 MHz, 151.8 MHz and 152 MHz), aeronautical navigation (245.5 MHz, 248.7 MHz and 249 MHz) and fixed mobile (605 MHz, 608.3 MHz, 612.2 MHz and 613.3 MHz).…”
Section: Introductionmentioning
confidence: 99%
“…The rest of the spectrum has been allocated for other purposes, such as telecommunication, radio and TV transmission, and many more, which sometimes interfere with radio astronomical observations. However, we are appreciative to the international union for sparing the hydrogen lines (HI) frequency for radio astronomy study and that this remains protected for astronomers to further study this spectrum and the Universe (Abidin et al, 2009(Abidin et al, , 2010(Abidin et al, , 2013. http://pkas.kas.org…”
Section: Spectrum Managementmentioning
confidence: 99%
“…At the same time, in [9] have done a survey of Hydrogen lines around 1300MHz-1500MHz and investigate the RFI in this band. They found frequency between 1380MHz-1400MHz is very important window for radio astronomy.…”
Section: Introductionmentioning
confidence: 99%